ANALYSIS OF THE INFLUENCE OF APIP BEHAVIOR PRINCIPLES ON AUDIT QUALITY (STUDY CASE OF THE INSPECTORATE JENDERAL OF THE MINISTRY OF COMMUNICATION AND INFORMATION) - Pratiwi, Leni; Jan Hoesada (Dinasti Publisher, 2020)
The purpose of this study is to obtain empirical evidence about the Analysis of the Effect of the APIP Behavior Principles (Integrity, Objectivity, Confidentiality, and Competence) on Audit Quality. This research was conducted at the Inspectorate General of Communication and Information. The independent variable in this study is the principles of APIP behavior (Integrity, Objectivity, Confidentiality, and Competence), and the dependent variable is Audit quality. The results of this study prove that the principles of APIP behavior affect audit quality.